Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Smkn 1 Papalang Kecamatan Papalang Kabupaten Mamuju - Pitriani, Pitriani; Madani, Muhlis; Mustari, Nuryanti (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to find out the effect of headmaster’s leadership on the performance of teachers at SMKN 1 Papalang, Papalang Sub-district, Mamuju Regency. This study used quantitative methods. Sampling technique used saturated sampling in which all member of the opulation was used as samples. Research data were questionnaires and observations. The data were analyzed by using descriptive statistical analysis with SPSS. The results of this study showed that the influence of headmaster’s leadership on the performance of teachers at SMKN 1 Papalang, Papalang Sub-district, Mamuju Regency was very significant. Therefore, the hypothesis in the study was accepted because it was supported by the significance value. So in other words the independent variable of the headmaster’s leadership was able to explein the magnitude of the dependent variable of teacher performance.